Pengembangan Kurikulum dengan Pendekatan Kurikulum Backward-Design - Martina Labora nainggolan; Yusniarti Situmorang; Justice Z Panggabean (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Curriculum development plays an essential role in improving the quality of education as it serves as a guideline for the implementation of teaching and learning processes. One of the approaches that can be applied in curriculum development is Backward Design, developed by Grant Wiggins and Jay McTighe. This approach places the desired learning outcomes as the starting point of instructional planning, followed by the determination of assessment methods and the design of appropriate learning activities. This study aims to describe the concept of Backward Design, its stages of development, its advantages and challenges, as well as its relevance to Christian Religious Education. The study employs a library research method with a qualitative descriptive approach through the analysis of books, journals, and other relevant scholarly sources. The findings indicate that Backward Design creates alignment between learning objectives, assessment, and instructional activities, resulting in a more focused and meaningful learning process. Furthermore, this approach promotes deep understanding, authentic assessment practices, and the development of students’ critical thinking skills. In the context of Christian Religious Education, Backward Design is highly relevant in helping teachers design learning experiences that foster faith development, character formation, and the application of Christian values in daily life. Therefore, Backward Design can serve as an effective alternative for curriculum development and the enhancement of educational quality.